2004
DOI: 10.1007/s10811-004-5505-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of phytoplankton characteristics in Tolo Harbour, Hong Kong, by HPLC analysis of chemotaxonomic pigments

Abstract: Spatial and seasonal characteristics of phytoplankton in Tolo Harbour, Hong Kong, were studied by microscopic observation of phytoplankton samples and HPLC analysis of chemotaxonomic pigments. Diatoms dominated the phytoplankton. Common diatoms included Skeletonema costatum and species of Cerataulina, Leptocylindrus, Pseudo-nitzschia and Thalassiosira. Dinoflagellates occurred sporadically and mainly in the inner part of the harbour. The dinoflagellate Scrippsiella trochoidea was the causative organism for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The presence of Cryptomonas spp . in Tolo Harbour has been confirmed previously by microscopic observations (Lam & Ho, 1989) and by the detection of alloxanthin (Yung et al , 1997; Wong & Wong, 2004). Cryptomonads, in sizes ranging from 3 to 50 µm, have a tendency to become more abundant when the abundance of other species decreases (Klaveness, 1988).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of Cryptomonas spp . in Tolo Harbour has been confirmed previously by microscopic observations (Lam & Ho, 1989) and by the detection of alloxanthin (Yung et al , 1997; Wong & Wong, 2004). Cryptomonads, in sizes ranging from 3 to 50 µm, have a tendency to become more abundant when the abundance of other species decreases (Klaveness, 1988).…”
Section: Discussionsupporting
confidence: 61%
“…Their observation was corroborated by that of Lam & Ho (1989) who reported a shift in the composition of the phytoplankton from diatoms to dinoflagellates in Tolo Harbour over the period from 1982 to 1985. However, several more recent studies found no evidence of a change in the composition of the phytoplankton community in Tolo Harbour (Yung et al , 1997; Wong & Wong, 2004). Lie et al (2011) suggested that shifts in N:Si ratios affected the abundance of diatoms in Tolo Harbour, but presented no evidence to show that the effect was strong enough to alter the dominance of diatoms.…”
Section: Discussionmentioning
confidence: 96%
“…Diatoms and dinoflagellates, the most abundant algal groups in Tolo Harbor Lam and Ho, 1989;Yung et al, 1997;Wong and Wong, 2004), are readily identifiable with microscopy in samples preserved in Lugol's fixative. The densities of small algal groups such as cryptomonads and small flagellates have increased markedly during the period from 1982 to 1992 (Yung et al, 1997), but their importance has not been fully recognized due to lack of taxonomic expertise and uncertainty associated with microscopic counts.…”
Section: Discussionmentioning
confidence: 99%
“…An Agilent Eclipse XDB-C18 polymeric reversed phase column (4.6 mm ID × 25 cm, 5 μm particle size) with a flow rate of 1.0 mL min -1 was used to provide selection for structurally similar phytopigment compounds with fine difference in molecular pattern (Van Heukelem et al, 1992).The mobile phase setups and injection of samples into the HPLC system were based on the procedures described by Wong and Wong (2004).…”
Section: Hplc Pigment Analysismentioning
confidence: 99%
“…The dominance of small copepods and the decrease in copepod abundance may have significant impact on the size structure of the phytoplankton community (Bruno et al , 1983; Bergquist et al , 1985; Vanni, 1987). Previous studies of marine plankton in Tolo Harbour have focused mainly on the taxonomic composition and seasonal dynamics of phytoplankton (Lam & Ho, 1989; Wong & Wong, 2004) and copepods (Wong et al , 1993; Zhang & Wong, 2011), with little or no information on the phytoplankton primary and copepod production in Tolo Harbour.…”
Section: Introductionmentioning
confidence: 99%